Awkward rituals: sensations of governance in Protestant America - Logan, Dana Wiggins (Class 200, new studies in religion, 2022)
Introduction -- Uncomfortable rites in Early Republican Freemasonry -- Conventional behavior in the America Bible Society -- Involuntary association in the American Seamen's Friend Society -- The head and the hands in Catharine Beecher's domesticity -- Epilogue : awkward ritual, once more with feeling.